Endothelial lipase genetic polymorphisms and the lipid-lowering response in patients with coronary artery disease on rosuvastatin. Issue 1 (December 2016) - Cai, Gaojun; Zhang, Bifeng; Shi, Ganwei; Weng, Weijin; Yang, Liping; Xue, Sheliang
Abstract Background Endothelial lipase (EL) plays an important role in the regulation of lipid metabolism by reducing the high density lipoprotein cholesterol (HDL-C) levels and inducing the macrophages to take up native low density lipoprotein cholesterol (LDL-C). Our purpose was to investigate the impact ofEL genetic polymorphisms on the lipid-lowering effects of rosuvastatin in Chinese coronary artery disease (CAD) patients. Methods One hundred twenty-one unrelated CAD patients, who underwent the treatment with rosuvastatin (10mg/day) for four to eight weeks, were enrolled in this study. Before and after treatment, serum lipids levels were measured. Genotypes ofEL 2037T/C and 2237 G/A polymorphisms were detected by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. Results Patients withEL 2037C allele (CC + CT) had significantly lower LDL-C levels than those with TT genotype (CC + CT: 2.60 ± 0.74 mmol/l; TT: 2.90 ± 0.87 mmol/l;P = 0.047), before rosuvastatin treatment. No significant differences between baseline lipid levels and theEL 2237G/A genotypes were observed. After treatment with rosuvastatin, total cholesterol (TC), high triglyceride (TG) and LDL-C levels decreased from baseline, on average, by 23.09 % (4.59 ± 0.96 mmol/l to 3.47 ± 0.83 mmol/l), 6.36 % (2.01 ± 1.18 mmol/l to 1.68 ± 1.16 mmol/l), 32.48 % (2.77 ± 0.83 mmol/l to 1.79 ± 0.62 mmol/l), respectively (allP < 0.05) in all patients. While changes in HDL-C levels did not reach statistical significance. No significant effects ofEL 2037T/C or 2237G/A polymorphism were observed on lipid-lowering effects of rosuvastatin. Conclusions EL 2037T/C and 2237 G/A polymorphisms might not affect the lipid-owing effects of rosuvastatin in Chinese CAD patients.